2019
DOI: 10.1007/s11096-019-00825-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a clinical medication review in vulnerable older patients at hospital discharge, a randomized controlled trial

Abstract: Background Drug-related problems (DRP) following hospital discharge may cause morbidity, mortality and hospital re-admissions. It is unclear whether a clinical medication review (CMR) and counseling at discharge is a cost-effective method to reduce DRP. Objective To assess the effect of a CMR on health care utilization and to investigate whether CMR is a cost-effective method to reduce DRP in older polypharmacy patients discharged from hospital. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Abbreviations: mdrev, medication review; mdrec, medication reconciliation; pedu, patient education/medication counseling; hpedu, health professional education; vm, use of validated methods; cds, use of Computerized Decision Support; ca, compliance aid; tc, transitional care compliance, (c) study-related involvement in medication management may have increased the complexity of care causing anxiety, confusion or dependence on health services, or (d) chance (type I error). 29,43 A strength of this study is the application of standard NMA as well as CNMA, in which we determined the effect of both the individual intervention components and the combinations of these components. Medication review is a very heterogeneous strategy and we investigated which particular combination of components of a medication review was most effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abbreviations: mdrev, medication review; mdrec, medication reconciliation; pedu, patient education/medication counseling; hpedu, health professional education; vm, use of validated methods; cds, use of Computerized Decision Support; ca, compliance aid; tc, transitional care compliance, (c) study-related involvement in medication management may have increased the complexity of care causing anxiety, confusion or dependence on health services, or (d) chance (type I error). 29,43 A strength of this study is the application of standard NMA as well as CNMA, in which we determined the effect of both the individual intervention components and the combinations of these components. Medication review is a very heterogeneous strategy and we investigated which particular combination of components of a medication review was most effective.…”
Section: Discussionmentioning
confidence: 99%
“…25,29,32,34 In the majority of the studies, at least half of the study population was female (n = 19, 76%). [25][26][27][28][29][31][32][33][35][36][37][38][39][40][43][44][45]48,49 In four studies (16%), 28,29,42,43 the intervention was community based within 2 weeks of discharge. The duration of follow-up of all studies varied from 4 weeks to 1 year.…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 33 primary studies which were reported in conference abstracts, trial protocols, journal articles and evaluation reports, 13 were conducted in the UK, 20 23 34–44 10 in the USA, 18 19 45–52 6 in Australia, 17 22 53–56 3 in the Netherlands 57–59 and 1 in Canada. 21 Multiple papers or reports could be related to the same original study.…”
Section: Resultsmentioning
confidence: 99%